Measuring and managing factors influencing sales performance : The study of petronas lubricant products / Mohamad Jais Daud ... [et al.] - Daud, Mohamad Jais; Saidi, Shairul Fahme; Amit, Sharkawi (2009)
The main product for this paper is PETRONAS lubricant in term of sales performance, and this paper is to indicate the interconnection among the product pricing, product quality and sales performance. Product pricing and product quality factors do contribute towards the sales performance of PETRONAS lubricant product. There are three main objectives of this paper. The first one is to investigate the relationship between the product quality factors and sales performance, then followed by determining the product price factors and sales performance. At the end of the paper, few recommendations have been made to further improve the sales performance of PETRONAS lubricant product.